Tolerance of Sitophilus zeamais (Coleoptera: Curculionidae) to heated controlled atmosphere treatments. (May 2015) - Li, Wei; Wang, Kun; Chen, Long; Johnson, Judy A.; Wang, Shaojin
Abstract: Combination heat and controlled atmosphere (CA) postharvest phytosanitary treatments are environmentally friendly alternatives to chemical fumigants. A controlled atmosphere/heating block system (CA-HBS) was used to rapidly assess tolerances of adult maize weevil, Sitophilus zeamais, both under regular air (RA) and CA (1% O2 and 15% CO2 ) conditions. In the RA treatment, thermal death kinetics for S. zeamais adults were determined at temperatures between 46 °C and 52 °C at a heating rate of 5 °C/min. The results showed that thermal death curves of S. zeamais adults followed a 0th-order kinetic reaction model. The required holding times for achieving 100% mortality were 165, 40, 14, and 4 min at 46, 48, 50 and 52 °C, respectively. The activation energy for killing S. zeamais adults was 526.7 kJ/mol. The effects of CA at various temperature-time combinations and heating rates on insect mortality were evaluated. The mortality of S. zeamais adults was higher under CA treatment than in the heat treatment alone. The slowest heating rate (0.1 °C/min) achieved the highest insect mortality in CA treatments but lowest mortality in RA treatments. The information obtained from the CA-HBS can be used to develop combination heat and CA treatments against S. zeamais. Highlights: CA-HBS was useful in rapidly assessing tolerance of Sitophilus zeamais. Thermal death curves of S. zeamais followed a 0th-order kinetic reaction model. Mortality of S. zeamais was higher under CA than heat treatment alone. Heating at 0.1 °C/min achieved highest mortality in CA but lowest in RA treatments.